Analysis of Factors Impeding Legal Optimization in the Settlement of Land Disputes through Mediation in Biau District, Buol Regency - Mohamad Ifan Ridwansyah (Universitas Negeri Gorontalo, 2023)
The purpose of this study is to determine what factors impede the optimization of the law of land dispute resolution through mediation in biau district, buol Regency. This study uses empirical research methods using a qualitative approach. The result of this study is that the Biau District Office of Buol Regency has performance problems in resolving land disputes through mediation which is an important factor because it is one of the districts located in the capital of Buol Regency. The Biau district government in handling land dispute mediation cases is not optimal and efficient in its performance of its duties, especially in resolving disputes will greatly affect the success of agrarian cases in biawu district. One of the main problems that occurred in 2018, 2019, and 2020 is a problem that almost every year increases. This can be a reference to Article 12 paragraph 5 which states that disputes or conflicts are not the authority of the Ministry of Agrarian affairs, for that the district government can mediate against people who have cases or agrarian problems.